Glacial geology of the Western Catskills - Kirkland, James Totten (The Open Repository @ Binghamton (The ORB), 1973)
Ic0 flow directions on the glaciated Appalachian Plateau in central New York were from the Adirondack Hountains. This is demonstrated by both striae directions and erratic provena.-1ce studies. No evidence for more than one Wisconsin glaciation as suggested by Rich (1935) could be found. Theories for local glaciation during the decline and after the retreat of the Laurentide Ice Sheet were also unsubstantiated. The East and West Branches Delaware River had different styles of daglaciation. The West Branch is characterized by zones of stagnation. The length of a zone is controlled by relief of the valley and corresponds to that length of ice confined within the valley. Stagnation of a zone results from the difference in the ability of ice to flow within the confines of a valley as ·compared with ice on the uplands. Each zone contains a number of sequences consisting of a graation from outwash to kame moraine to kame terrace. Within a given zone there is a vertical succession of ka.rne terraces and a corresponding horizntal succession of krone moraines. Kame moraines occur at the junctions of tributaries to the West Branch and deri.ved much of' their sediments from them. Reconstructed ice profiles for the sequences demonstrate that the ice forming the sequences was stagnant at the time of sequence formation. 'he East Branch appears to have been the site of more massive stagnation caused by·topographic detachment of lee :from the retreating ice sheet. Three different lakes were formed with progressive stagnation of ice up the East Branch. The most conspicuous features associated with the different lakes are kame deltas. The kame deltas formed at the junction of tributaries with the East Branch and their sediments reflect both an ice and an upland source. Three main units are recognized for karne deltas in the East Branch: (1) A lower sequence which prograded outward between the ice and the valley wall. (2) Overlying steeply dipping silt forest beds from sediment originating in the uplands. (3) A .ripple-drift section representing late stage sedimentation bv meltwaters from the ice.